2014
DOI: 10.1371/journal.pone.0101709
|View full text |Cite
|
Sign up to set email alerts
|

Harmful Effects of the Azathioprine Metabolite 6-Mercaptopurine in Vascular Cells: Induction of Mineralization

Abstract: Vascular mineralization contributes to the high cardiovascular morbidity and mortality in patients who suffer from chronic kidney disease and in individuals who have undergone solid organ transplantation. The immunosuppressive regimen used to treat these patients appears to have an impact on vascular alterations. The effect of 6-mercaptopurine (6-MP) on vascular calcification has not yet been determined. This study investigates the effect of 6-MP on vascular mineralization by the induction of trans-differentia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 45 publications
6
18
0
Order By: Relevance
“…Extracellular calcium content of different vascular beds was determined as previously published [ 10 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular calcium content of different vascular beds was determined as previously published [ 10 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several indications exist that AZA treatment has an impact on the cardiovascular risk and pathophysiology of the vessel wall [ 8 , 9 ]. In a previous study, we found an induction of mVC and oxidative stress upon treatment with the cleavage product of AZA, 6-mercaptopurine (6-MP), using an in vitro model with rat VSMCs [ 10 ]. Extensive research in the field of VSMC calcification revealed the involvement of several mechanisms including osteogenic, senescence and inflammatory signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, aortic rings from rats and mice are commonly used for studying vessel calcification under various conditions. The stimulation time varies from 3-14 days [6,24,25,28,59,[62][63][64][65]. Although the utilization of aortic rings comes closer to the physiologic setting, a multitude of influencing factors is still lost.…”
Section: Ex Vivo Modelsmentioning
confidence: 99%
“…8 Using in vitro and ex vivo models, a study published in 2014 demonstrated that 6-mercaptopurine can induce phenotypic transformation of vascular smooth muscle cells, which would predispose patients to arteriosclerosis, potentially increasing the risk of cardiovascular events. 72 Anti-TNF agents do not seem to modify cardiovascular risk in observational studies in IBD; whether this finding represents a true inability to modify cardiovascular risk with treatment of systemic inflammation, or simply an inability to account for confounding by disease severity remains unclear. For instance, a comparable risk of CHD was seen in patients treated with anti-TNF agents (IRR 0.60, 95% CI 0.25-1.44) and in patients not on anti-TNF agents (IRR 1.24, 95% CI 1.16-1.32), using patients without IBD as a reference.…”
Section: Ibd-directed Therapymentioning
confidence: 99%